2000
DOI: 10.1016/s0039-6028(99)01057-2
|View full text |Cite
|
Sign up to set email alerts
|

Local electronic structure of intrinsic defects and impurities at the Fe(001) surface

Abstract: Local electronic structure of intrinsic defects and impurities at the Fe (001) Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. AbstractAb-initio calculations for the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…As shown in Table 3, Fe2 atoms have only four nearest-neighboring Fe3 atoms. This agrees with the fact that reduction of the number of nearest-neighboring and/or next nearest-neighboring atoms increases local magnetic moments, as shown for the surface Fe atoms in the literature [44]. The Fe3 atoms are neighboring to 10 Fe and 3 C atoms, which is similar to the Fe atoms in hFe 3 C. The magnetic moment of Fe3 atoms is 1.78 l B , a value which is the smallest in the compound and is close to that in h-Fe 3 C. Fe4 atoms also have 10 Fe neighbors ranging from 2.38 to 2.61 Å , and two C neighbors (Fe-C bond of 2.10 Å ).…”
Section: Electronic Structure Of C-fe 23 Csupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Table 3, Fe2 atoms have only four nearest-neighboring Fe3 atoms. This agrees with the fact that reduction of the number of nearest-neighboring and/or next nearest-neighboring atoms increases local magnetic moments, as shown for the surface Fe atoms in the literature [44]. The Fe3 atoms are neighboring to 10 Fe and 3 C atoms, which is similar to the Fe atoms in hFe 3 C. The magnetic moment of Fe3 atoms is 1.78 l B , a value which is the smallest in the compound and is close to that in h-Fe 3 C. Fe4 atoms also have 10 Fe neighbors ranging from 2.38 to 2.61 Å , and two C neighbors (Fe-C bond of 2.10 Å ).…”
Section: Electronic Structure Of C-fe 23 Csupporting
confidence: 91%
“…For all iron atoms, the Fermi level is at the top of the Fe 3d states for the spin-up electrons. Therefore, the Fe atoms are almost fully spin-polarized, in line with electronic structure of a-Fe [44,45].…”
Section: Electronic Structure Of C-fe 23 Csupporting
confidence: 55%
See 1 more Smart Citation
“…7 Another possibility is that it originates from different chemical species, carbon or oxygen atoms. 15 However, the latter one is excluded since the difference of the chemical species must lead to that of the surface state energy as well as the peak intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Impurity atoms, e.g., carbon and oxygen, included in bcc-͑001͒ surfaces shift the surface state energy. 14,15 Other origin is that confinement effect induced by surface atomic arrangements gives rise to the surface state shift. Biedermann et al showed that one-dimensional localization of Fe atoms, which was surrounded by Si atoms on FeSi͑001͒ surfaces, induced surface state shift from 0.3 to 0.6 eV above the Fermi level.…”
Section: In Detailmentioning
confidence: 99%